Branding Pendidikan Lingkungan Berbasis Pengelolaan Sampah dan Infrastruktur Dasar di Sekolah Rakyat Terintegrasi 45 Semarang Jawa Tengah - Sofia, Evi; Rika Sa'diyah (Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to strengthen environmental education branding through basic education on waste management and the introduction of basic infrastructure to students of Sekolah Rakyat Terintegrasi 45 Semarang, Central Java. The target participants were 44 elementary school–aged students, with the involvement of elementary and senior high school teachers within the school environment. The activity was conducted on December 2, 2025, in commemoration of Public Works (PU) Devotion Day through the DWP Mengajar program with the theme “Educating with Heart, Inspiring the Nation.” The implementation method employed a participatory educational approach as a strategy for environmental education branding, delivered through interactive learning sessions, simple discussions, educational games, and waste management simulations. The results indicated an improvement in students’ understanding of waste classification, the importance of maintaining environmental cleanliness, and awareness of the functions of basic infrastructure such as roads, drainage systems, and waste management facilities. Furthermore, the activity contributed to the development of environmentally caring character traits and the adoption of clean and healthy living habits from an early age. Therefore, education on waste management and basic infrastructure proved to be effective as a contextual learning medium for instilling environmental awareness values among Sekolah Rakyat students.